Adnan Mehmeti - The poet of the Albanian diaspora in the United States of America - Muhadri, Besim (Technium Social Sciences Journal, 2023)
Most of the Albanian literary creators who live and work in the United States of America have experienced their affirmation in their homeland, however, in the case of their exile in the United States of America, they have continued their passion for literary art here. creating important works for the Albanian community, but also for the American one. Adnan Mehmeti is one of those Albanian poets, who will reach his affirmation in the field of letters in the United States of America. He has published several books of poetry, but also non-fiction books. His poetry has been translated into several languages, including English, Spanish, Romanian, and Swedish, and has been featured in several poetry anthologies. He is also the winner of several prestigious literary awards. Adnan Mehmeti works and lives in the United States and is the president of the Association of Albanian-American Writers.